Value Creation through Acquisition Strategy: A Study of Volvo’s Acquisition by Geely - Chandera, Yane; Widjojo, Handyanto (International Research Journal of Business Studies, 2012)
This paper examines the value creation on the acquisition of Volvo Car Corp by Zhejiang Geely Holding Group. The acquisition of Volvo by Geely became an interesting topic to discuss since it was the first time in automotive industry that a Chinese company acquired an international company with a considerably high transaction amount. The paper examines the short term value creation using event study to calculate abnormal returns of each company’s stock during the announcement period and measuring the significance of the cumulative abnormal return. The findings are consistent with previous studies over the years which have shown that most acquisitions fail to add value for shareholders in the acquiring company. The paper discusses the broad managerial implications of the findings this paper discussion on marketing aspect after the acquisition by integrating two different brand perceptions.